Reconstruction of Arbitration Agreement Arrangements to Prevent Pathological Arbitration Clauses in Indonesia - Meydora Cahya Nugrahenti; Herliana Herliana; Rr. Retno Sugiharti (Jurnal Pembangunan Hukum Indonesia, 2025)
Pathological arbitration clauses can hinder the arbitration process and open up opportunities for the parties to avoid arbitration or challenge its decision. These clauses may arise due to deliberate intent or a lack of understanding on the part of the parties. Law No. 30 of 1999 on Arbitration and Alternative Dispute Resolution (AAPS Law) does regulate arbitration agreements, but it is not comprehensive in preventing the emergence of pathological clauses. This study aims to identify forms of pathological arbitration clauses that hinder the effectiveness of arbitration and to formulate a reconstruction of arbitration agreement regulations to prevent them in Indonesia. The research method used is juridical-normative with an emphasis on legal norms as the main object. The data used consists of primary and secondary legal materials through legislative, analytical, comparative, and conceptual approaches. The results of the study show that pathological arbitration clauses hinder arbitration because they contain ambiguities, such as unclear arbitration authority to resolve disputes, the existence of options for the parties to choose a court, and the appointment of unavailable arbitrators. To prevent pathological arbitration clauses, Article 9 of the AAPS Law needs to be reconstructed by including arbitration clause regulations that explicitly state the authority of arbitration without exception. The conclusion of this study is that there are pathological clauses in the agreement and therefore the reconstruction of Article 9 of the AAPS Law is carried out by providing legal certainty on the pactum de compromittendo in the arbitration agreement.